2017
DOI: 10.1007/s10517-017-3620-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Level of Circulating hsa-miR-297 and hsa-miR-19b-3p miRNA Are Associated with Generalization of Prostate Cancer

Abstract: We performed diagnostic classification of plasma specimens from patients with non-metastatic and metastatic prostate cancer based on pairs of miRNA that have no individual diagnostic significance. Of 230 miRNA detected in plasma specimens, 3 pairs were diagnostically significant. The miRNA pair hsa-miR-19b-3p and hsa-miR-297 demonstrated highest sensitivity and specificity. Among common target genes of these miRNA, CFL2 gene associated with cell mobility was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…On the other hand, this miRNA is frequently down-regulated in KiC tissues and its restoration was considered as a potential therapeutic strategy for KiC therapy 75 . The up-regulation of hsa-mir-19b-3p demonstrated highest diagnostic sensitivity and specificity in PrC 76 . It has been found that hsa-mir-19b-3p is highly expressed in BlC 77 and its enrichment has been described as being directly associated with KiC 78 .…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, this miRNA is frequently down-regulated in KiC tissues and its restoration was considered as a potential therapeutic strategy for KiC therapy 75 . The up-regulation of hsa-mir-19b-3p demonstrated highest diagnostic sensitivity and specificity in PrC 76 . It has been found that hsa-mir-19b-3p is highly expressed in BlC 77 and its enrichment has been described as being directly associated with KiC 78 .…”
Section: Discussionmentioning
confidence: 95%
“…Several panels of miRNAs were already introduced to ESCC detection [ 102 ]. Plasma levels of miRNA pair miR-19b-3b and miR-297-5p were found to be diagnostically significant for prostate cancer [ 103 ]. A combination of exosomal miR-126-3p, miR-449a-5p, and miR-34b-5p was adopted to the diagnosis of ccRCC, and combination of miR-126-3p and miR-34b-5p could identify carcinoma and benign injury [ 71 ].…”
Section: The Disadvantage and Limitation Of Circulating Mirnas As Diamentioning
confidence: 99%
“…MiRNA expression levels are usually altered and associated with pathological conditions [ 39 , 40 ]. There are more distinct miRNAs expressed in the brain than in any other organ, implying a complex regulation network [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%